PENILAIAN GURU PAMONG TERHADAP KOMPETENSI MAHASISWA PLK DI SMK NEGERI 5 PADANG - 1640-1653 , Arif Aprinal (Universitas Negeri Padang, 2016)
ABSTRACT This research was descriptive research which aimed to reveal student teachers’ competence based on supervisor teachers’ judgment at SMK N 5 Padang in the semester of July-December 2015 seen from pedagogical competence, personality competence, social competence, and professional competence. Population of this research was all supervisor teachers at SMK N 5 Padang who supervised the student teachers in the semester of July-December 2015. Technique of taking the samples used in this research was total sampling technique which involved 35 teachers. The data were collected using questionnaire with Likert Scale which consisted of 4 alternatives. There were 35 statements in the questionnaire of this research. From the result of the research, it was found that the degree of student teachers’ pedagogical competence was 51,44% with moderate category; the degree of student teachers’ personality competence was 57,14% with high category; the degree of student teachers’ social competence was 65,71% with moderate category; and the degree of student teachers’ professional competence was 62,85% with high category. Key Words: Competence, Student Teacher, Supervisor Teacher